ALCOHOL CONCENTRATION DETECTOR IN LIQUOR BASED ON MICROCONTROLLER - Mirtha Y. S. Risakotta; Ronaldo Talapessy; Rosita De Fretes (Pattimura University, 2017)
Has made an alcohol concentration detector based on microcontroller that can detect alcohol concentration in liquor is accurate, fast, stable and has a high sensitivity. In this research, use traditional liquor of Moluccas â€œSopiâ€, and liquors on the market. An alcohol concentration detector was built based on microcontroller ATmega16 which can receive and process data from the sensor MQ-3 in a form that can be converted into the form of an electrical signal and the output is displayed on the LCD. Calibration of the sensor MQ-3 shows that the greater the value of resistance sensor, the smaller the value of an alcohol concentration. The correlation of resistance sensor to alcohol concentration is plotted in a graph of linearity with R2 = 0,9982. The results of liquor on the market and Sopi (premium quality) had alcohol concentration ranging between 3 â€“ 5% per mL, while an alcohol concentration of Sopi (regular quality) is below 3% per mL.